Serocorrelates of protection against infant group B streptococcus disease. Issue 5 (May 2019) - Le Doare, Kirsty; Kampmann, Beate; Vekemans, Johan; Heath, Paul T; Goldblatt, David; Nahm, Moon H; Baker, Carol; Edwards, Morven S; Kwatra, Gaurav; Andrews, Nick; Madhi, Shabir A; ter Meulen, Ajoke Sobanjo; et al.
Summary: Group B streptococcus (GBS) is a leading cause of young infant mortality and morbidity globally, with vaccines being developed for over four decades but none licensed to date. A serocorrelate of protection against invasive disease in young infants is being considered to facilitate vaccine early licensure, followed by demonstration of efficacy assessed postlicensure. In this Review, we synthesise the available scientific evidence to define an immune correlate associated with GBS disease risk reduction on the basis of studies of natural infection. We summarise studies that have investigated GBS serum anticapsular or anti-protein antibodies, and studies measuring the association between antibody function and disease risk reduction. We highlight how knowledge on the development of correlates of protection from existing vaccines could be harnessed to facilitate GBS vaccine development. These lessons include aggregation of serocorrelates of protection for individual serotypes, understanding the relationship between immunity derived from natural exposure of adults and vaccine-induced immunity, or using extrapolation of protection from in-vitro immunoassay results. We also highlight key considerations for the assessment of the role of antibodies to derive a serocorrelate of risk reduction in future seroepidemiological studies of GBS disease.